2011
DOI: 10.4196/kjpp.2011.15.6.353
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Potential of Cyanidin-3-glucoside Fraction Extracted from Mulberry Following Oxygen-glucose Deprivation

Abstract: In this study, cyanidin-3-glucoside (C3G) fraction extracted from the mulberry fruit (Morus alba L.) was investigated for its neuroprotective effects against oxygen-glucose deprivation (OGD) and glutamate-induced cell death in rat primary cortical neurons. Cell membrane damage and mitochondrial function were assessed by LDH release and MTT reduction assays, respectively. A time-course study of OGD-induced cell death of primary cortical neurons at 7 days in vitro (DIV) indicated that neuronal death was OGD dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 40 publications
(52 reference statements)
0
31
0
Order By: Relevance
“…All these data suggest that C3G can induce neuroprotection against glutamate-induced cell death by Ca 2þ -dependent [Zn 2þ ] i increase through mitochondrial depolarization and formation of ROS. C3G has been reported to have a neuroprotective effect against neuronal cell death in oxygen glucose deprivation-induced cell death in rat cortical neurons (Bhuiyan et al, 2011(Bhuiyan et al, , 2012Kang et al, 2006). However, in Bhuiyan et al's studies (2011), C3G (10 μg/ml) was reported to have no inhibitory effects on glutamate-induced neuronal cell death in cultured cortical neurons.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…All these data suggest that C3G can induce neuroprotection against glutamate-induced cell death by Ca 2þ -dependent [Zn 2þ ] i increase through mitochondrial depolarization and formation of ROS. C3G has been reported to have a neuroprotective effect against neuronal cell death in oxygen glucose deprivation-induced cell death in rat cortical neurons (Bhuiyan et al, 2011(Bhuiyan et al, , 2012Kang et al, 2006). However, in Bhuiyan et al's studies (2011), C3G (10 μg/ml) was reported to have no inhibitory effects on glutamate-induced neuronal cell death in cultured cortical neurons.…”
Section: Discussionmentioning
confidence: 89%
“…All these data suggest that C3G inhibits glutamate-induced [Zn 2þ ] i increase by inhibiting formation of ROS through Ca 2þ -dependent mitochondrial depolarization, but not by ROS-dependent mitochondrial depolarization. In fact, the mulberry C3G (Bhuiyan et al, 2011) and black soybean C3G (Bhuiyan et al, 2012) have been reported to prevent OGD-induced mitochondrial depolarization in primary cortical neurons. In this study, while intracellular Zn 2þ chelator TPEN markedly inhibited glutamateinduced [Zn 2þ ] i increase, it tended to inhibit, but not significantly, glutamate-induced mitochondrial depolarization.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Immunocytochemical staining with anti-NeuN and anti-GFAP antibodies revealed that the cell cultures contained approximately 99% neurons. 29) Preliminary experiments showed that DIV-10 neurons seemed to be more resistant to OGD injury than DIV-7 neurons (data not shown). Therefore, we performed a time course study of OGD-induced cell death in DIV-7 cells, and neuronal injury was quantified by MTT reduction assay 24 h after OGD.…”
Section: Resultsmentioning
confidence: 95%
“…MTT [3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide, Duchefa Biochemie, Haarlem, The Netherlands] is converted to the blue formazan product by metabolically active mitochondria, and the reaction is proportional to the number of viable cells [20,21]. Astrocytes were cultured in 96-well culture plates for 24 h and chemical ischemia was induced for 1, 2, 3, and 6 h. MTT (0.5 mg/ml) was added to the control and the ischemia-treated wells of the culture plate.…”
Section: Methodsmentioning
confidence: 99%